Islamic Ecotheology and Sustainable Agriculture in Indonesia: A Thematic Analysis of The Interpretation of The Archipelago - Abdunna'im Al Husaini; Ahmad Nurrohim (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to formulate a theological integration model that is applicable to environmental governance by exploring the operationalization of Islamic Eco theological principles in sustainable agricultural policies in Indonesia. The method used is descriptive qualitative through library research. The analysis was carried out thematically (maudhu’i) using content analysis and comparative hermeneutics methods on primary texts, namely Tafsir Al-Azhar by Hamka and Tafsir Al-Misbah by M. Quraish Shihab. The analytical knife is equipped with the framework of Maq??id al-shar??ah to transform sacred texts into practical policy recommendations. The results show that the pillars of Islamic ecotheology consisting of M?z?n (cosmic balance), Khil?fah (ethical governance), and Am?nah (moral accountability) provide a solid normative architecture for the agrarian system. Hamka and Quraish Shihab's thoughts converge on the values of ecological justice and interdependence between beings. Through the framework of Maq??id al-shar??ah, these theological values have been successfully operationalized into practical policies, such as Climate-Smart Agriculture, agroforestry, sustainability certification (ISPO/RSPO), as well as green financial instruments in the form of zakat, environmental waqf, and carbon taxes. The conclusion of the study emphasizes that the success of sustainable agriculture and agrarian justice for smallholders in Indonesia cannot be solved only through a technocratic approach, but requires moral-spiritual integration. This research contributes to expanding the discourse of Maq??id al-shar??ah to the macroecological dimension and offers a paradigm of "Ecological Sovereignty" to deal with the cross-border climate crisis.